Spatial and Temporal Distribution of Culex and Aedes mosquitoes in Ghana - Owusu-Asenso, Christopher Mfum; Afrane, Yaw Asare; Akuamoah-Boateng, Yaw; Abdulai, Anisa; Sabtiu, Abdul Rahim Mohammed; Sraku, Isaac Kwame; Mensah, Sebastian Kwo Egyin; Owusu, Faustina Adobea; Addo, Margaret; Ebuako, Abena Ahema; Akuoko, Osei Kwaku; Akosah-Brempong, Gabriel; et al. (My University, 2025)
In Africa, Culex is an important vector that transmits West Nile Virus whilst Aedes mosquitoes transmits dengue, yellow fever, chikungunya and zika. There is however very limited data on their bionomics and ecology. Here, we provide data on the abundance and distribution of Culex and Aedes mosquitoes in Ghana from 2017 – 2025. We collected 39,761 Culex and 6,047 Aedes mosquitoes using various mosquito-trapping tools. Both vectors were predominantly observed outdoors. Aedes aegypti was the most dominant Aedes vector observed in Ghana. The invasive Aedes albopictus has recently been found from 2023 whereas Aedes vittatus was observed in Accra. Our data provides important information to support vector surveillance, ecological risk assessments, and integrated vector management strategies.